Systemic to Pulmonary Collateral Flow as Measured by Cardiac Magnetic Resonance Imaging is Associated with Acute Post-Fontan Clinical Outcomes - Glatz, Andrew C. (2012)
BACKGROUND: Systemic-pulmonary collateral (SPC) flow occurs commonly in single ventricle patients after superior cavo-pulmonary connection, with unclear clinical significance. We sought to evaluate the association between SPC flow and acute post-Fontan clinical outcomes using a novel method of quantifying SPC flow by cardiac magnetic resonance (CMR). METHODS AND RESULTS: All patients who had SPC flow quantified by CMR prior to Fontan were retrospectively reviewed to assess for acute clinical outcomes after Fontan completion. Forty-four subjects were included who had Fontan completion between May, 2008 and September, 2010. SPC flow prior to Fontan measured 1.5 ± 0.9 L/min/m(2), accounting for 31 ± 11% of total aortic flow and 44 ± 15% of total pulmonary venous flow. There was a significant linear association between natural log-transformed duration of hospitalization and SPC flow as a proportion of total aortic (rho=0.31, p=0.04) and total pulmonary venous flow (rho=0.29, p=0.05). After adjustment for Fontan type and presence of a fenestration, absolute SPC flow was significantly associated with hospital duration ≥ 7 days (OR=9.2, p=0.02) and chest tube duration ≥ 10 days (OR=22.7, p=0.009). Similar associations exist for SPC flow as a percentage of total aortic (OR=1.09, p=0.048 for hospitalization ≥ 7 days; OR=1.24, p=0.007 for chest tube duration ≥ 10 days) and total pulmonary venous flow (OR=1.07, p=0.048 for hospitalization ≥ 7 days; OR=1.18, p=0.006 for chest tube duration ≥ 10 days). CONCLUSIONS: Increasing SPC flow before Fontan, as measured by CMR, is associated with increased duration of hospitalization and chest tube following Fontan completion.